Behavior Of Pregnant Mothers To Prevent Malaria With Pre And Post Personal Counseling Methods - Hasnia Hasnia; Sri Ramadany; A. Arsunan Arsin; Yuyun Widaningsih; Muhammad Tamar (JKM (Jurnal Kebidanan Malahayati), 2022)
Background: : One of the public health problems that can increase maternal and infant mortality and morbidity is malaria. The risk of pregnancy complications can occur in every pregnant woman and can threaten her life, so pregnant women must know what these complications are by providing information according to the mother's needs related to pregnancy to be the right strategy to reduce the number of pregnancy complications. According to WHO, in 2015 the number of new cases found worldwide was 214 million cases and at the same time there were 438,000 cases of malaria which caused death. Based on data on Malaria Endemicity per Regency/City in Indonesia in 2018, the third level of malaria endemic districts is Papua Province, namely Jayapura, Yapen Islands, Mimika, Boven Digoel, Sarmi, Keerom (Indonesian malaria endemicity, 2018). Based on previous data on malaria patients who were examined by health workers through blood tests, the highest provinces were Papua (12.07%), West Papua (8.64%) and East Nusa Tenggara (1.99%). Based on the latest data on the number of positive malaria cases and the number of malaria infections (Annual Parasite Incidence/API), all malaria cases in 2019 in Indonesia were 250,644 cases and the incidence of malaria in pregnancy in 2019, Papua Province is the province in Indonesia with the highest number of cases in the 1769 category case.Destination: Analyzing the behavior of pregnant women towards malaria prevention with the method of pre and post personal counseling in the Working Area of the Sentani Health Center in 2022.Method: This type of research is quasi-experimental with a pre-post control design approach which approaches two groups, namely the intervention group by providing treatment (personal counseling) and the control group (leaflets). The data collected is primary data and secondary data with personal counseling variables as independent variables and changes in knowledge, attitudes and behavior as the dependent variable. The research sample was pregnant women as many as 33 respondents in each group. Sampling with purposive sampling technique in accordance with predetermined criteria. The instrument used is a knowledge, attitude and behavior questionnaire. Analysis of the data used is a non-parametric test, namely the Mc Nemar and Mann-Withney test .Results: There was a change in the knowledge of pregnant women on the prevention of malaria pre and post personal counseling at the Sentani Health Center, Jayapura Regency in the intervention group with the results of the calculation of x2 with the Mc Nemar distribution table using degrees of freedom 1 with a level of = 0.05 ie 3.841 obtained X 2 count 18 0.05 > 3.841 with a value of 0.000 < 0.05, while in the control group obtained X 2 count 7.04 > 3.841 with a value of 0.021 < 0.05 and there are differences in changes in pre-post knowledge in the two groups obtained a value of 0.011 < 0.05. There is a change in the attitude of pregnant women towards malaria prevention pre and post personal counseling at the Sentani Health Center, Jayapura Regency in the intervention group obtained X 2 count 25.03 > 3.841 with a value of 0.031 > 0.05, while in the control group obtained X 2 count 5.93 > 3.841 with a value of 1,000 < 0.05 and there are differences in pre-post attitude changes in the two groups obtained a value of 0.001 < 0.05. There is a change in the behavior of pregnant women towards malaria prevention pre and post personal counseling at the Sentani Health Center, Jayapura Regency in the intervention group obtained X 2 count 21.33 > 3.841 with a value of 0.031 > 0.05, while in the control group obtained X 2 count 6.32 > 3.841 with a value of 0.500 <0.05 and there is a difference in pre-post attitude changes in the two groups obtained a value of 0.013 <0.05.Conclusion: There was a change in knowledge, attitude and behavior of pregnant women after being given personal counseling about malaria prevention in the Sentani Health Center Work Area and there were differences in changes in knowledge, attitudes and behavior of pregnant women in the intervention group and the control group. Keywords : Behavior of pregnant women, malaria prevention, personal pre-counseling, personal post-counseling